Bringing stakeholders together for urban health equity: hallmarks of a compromised process - Katz, Amy S. (Int J Equity Health, 2015)
There is a global trend towards the use of ad hoc participation processes that seek to engage grassroots stakeholders in decisions related to municipal infrastructure, land use and services. We present the results of a scholarly literature review examining 14 articles detailing specific cases of these processes to contribute to the discussion regarding their utility in advancing health equity. We explore hallmarks of compromised processes, potential harms to grassroots stakeholders, and potential mitigating factors. We conclude that participation processes often cut off participation following the planning phase at the point of implementation, limiting convener accountability to grassroots stakeholders, and, further, that where participation processes yield gains, these are often due to independent grassroots action. Given the emphasis on participation in health equity discourse, this study seeks to provide a real world exploration of the pitfalls and potential harms of participation processes that is relevant to health equity theory and practice.